2017
DOI: 10.1111/poms.12672
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Management of Reusable Resources with Advanced Reservations

Abstract: W e consider a revenue management problem wherein the seller is endowed with a single type resource with a finite capacity and the resource can be repeatedly used to serve customers. There are multiple classes of customers arriving according to a multi-class Poisson process. Each customer, upon arrival, submits a service request that specifies his service start time and end time. Our model allows customer advanced reservation times and services times in each class to be arbitrarily distributed and correlated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Several studies that analyze online scheduling problems that are similar to the ORP assume that some distributional information on job arrivals and/or durations is available [12][13][14]. Because the focus in these studies is on exploiting the distributional information, we do not review them.…”
Section: Related Literaturementioning
confidence: 99%
“…Several studies that analyze online scheduling problems that are similar to the ORP assume that some distributional information on job arrivals and/or durations is available [12][13][14]. Because the focus in these studies is on exploiting the distributional information, we do not review them.…”
Section: Related Literaturementioning
confidence: 99%
“…In [6], authors solved class of revenue management problems in systems with reusable resources. The authors suggested 2approximation algorithm for revenue management models in which resources can be reused, and [7] was expanded so advance reservations are possible. Some authors use approximation algorithms for solving this problem.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The revenue management problems through the prism of dynamic pricing were also studied by Ladany and Arbel [72], Gallego and Van Ryzin [47,113], Feng and Gallego [39] and You [128]. Levi and Shi [77] and Chen et al [28] suggested efficient and simple heuristic approaches to revenue management of reusable resources with advanced reservations within the scope of queuing theory. The results in [28] are applicable for fixed prices as well as for variable prices.…”
Section: Combining Dynamic Pricing With Resource and Inventory Managementioning
confidence: 99%
“…Levi and Shi [77] and Chen et al [28] suggested efficient and simple heuristic approaches to revenue management of reusable resources with advanced reservations within the scope of queuing theory. The results in [28] are applicable for fixed prices as well as for variable prices.…”
Section: Combining Dynamic Pricing With Resource and Inventory Managementioning
confidence: 99%